The recipe for being a good military wife: how military wives managed OIF/OEF deployment - Aducci, C. J.; Baptist, Joyce A.; George, Jayashree; Barros, Patricia Cristina Monteiro de; Goff, Briana S. Nelson (My University, 2012)
Interviews with 25 military wives to elicit their lived experience of OIF/OEF deployment found two main themes: the recipe for being a good military wife and managing split loyalties. Military wives’ experience reflected a disenfranchised existence. Their stress was exacerbated by the reality of the composition of their marital relationship -- a couple-military threesome -- that they bore in silence. Their marginalization did not deter them from supporting their husbands the best they could, reflecting their inherent strength and resilience. The wives had a recipe that helped them manage the stresses inherent in deployment. Research and clinical implications are discussed.
Keywords: Military wives; Operation Iraqi Freedom/Operation Enduring Freedom deployment; Combat deployment; Qualitative research; Feminist epistemology; Military couples